Analisis Hasil Belajar Siswa ABK (Anak Berkebutuhan Khusus) Yang Bersekolah di SDN Mugarsari Kelas IV Dan VI - Fitria, Sumayah; Maftuh, Ade; Zahrah, Riza Fatimah (Journal Of Dehasen Educational Review, 2024)
The phenomenon of students with special needs who attend public schools is no longer a strange thing to the community. The problems that occur are because ABK students have difficulty in learning and are very slow in learning so that learning outcomes must pay attention to several considerations, namely teachers must pay attention to adjustments to the assessment of children with special needs, inclusion settings, learning outcome assessment criteria. The purpose of this study is to find out the learning outcomes of students, the factors that affect learning outcomes as well as the efforts and solutions made by teachers in improving the learning outcomes of ABK (Children with Special Needs) students at SDN Mugarsari grades IV and V. The research design used in this study is descriptive research using qualitative methods. The data collection techniques used in this study include observation, in-depth interviews and documentation. The data analysis method used in this study is to use a qualitative data analysis strategy by utilizing data triangulation. The results of the study showed that the learning outcomes of the three ABK students in grades IV and VI at SDN Mugarsari were ABK students with the initials (A) of 76.78, students with the initials (F) of 85.11 and students with the initials (U) of 70 where the score reached KKM. The factors that affect the learning outcomes of ABK students at SDN Mugarsari grades IV and VI are the first classroom environment, school environment and family environment. The second is learning time. The efforts/solutions made by teachers in overcoming learning difficulties for ABK students at SDN Mugarsari grades IV and VI are to provide motivation and provide guidance in a subtle, patient and thorough manner. Then using learning methods that attract the interests and talents of ABK students such as visual and audio learning methods. As well as creating a fun learning atmosphere so that ABK students do not feel bored during learning.